2013
DOI: 10.1007/s10533-013-9856-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fine litter chemistry on lignocellulolytic enzyme efficiency during decomposition of maize leaf and root in soil

Abstract: Residue recalcitrance controls decomposition and soil organic matter turnover. We hypothesized that the complexity of the cell wall network regulates enzyme production, activity and access to polysaccharides. Enzyme efficiency, defined as the relationship between cumulative litter decomposition and enzyme activities over time, was used to relate these concepts. The impact of two contrasting types of cell walls on xylanase, cellulase and laccase efficiencies was assessed in relation to the corresponding changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 49 publications
2
40
1
Order By: Relevance
“…The lowest enzyme efficiencies in the root treatment were compensated for by the highest investments in enzyme activities. The relationships between the enzyme efficiencies and the chemical recalcitrance of the substrate remain unclear (Sinsabaugh et al, 2002; Wickings et al, 2012; Amin et al, 2014; Fanin et al, 2016). In the present work, differences in the enzyme efficiencies observed between the stems and roots could not be explained by differences in the lignin content, which was similar for the two litters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest enzyme efficiencies in the root treatment were compensated for by the highest investments in enzyme activities. The relationships between the enzyme efficiencies and the chemical recalcitrance of the substrate remain unclear (Sinsabaugh et al, 2002; Wickings et al, 2012; Amin et al, 2014; Fanin et al, 2016). In the present work, differences in the enzyme efficiencies observed between the stems and roots could not be explained by differences in the lignin content, which was similar for the two litters.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the enzyme efficiencies between dates and summed the values over the entire incubation period for the C-acquiring hydrolase activity by summing the ÎČG, EX, and EG activities and for the oxidative enzyme activity by using the LAC value. The enzyme activity efficiencies can be assessed against the CO 2 mineralized as an index of microbial metabolism (Sinsabaugh et al, 2002; Moorhead et al, 2013b; Amin et al, 2014). We proposed in this study to calculate the efficiency of the enzyme activity for fungal-C biosynthesis (in ÎŒg fungal-C mol -1 ) by dividing the amount of recovered C in fungal biomass by the cumulative enzyme activity (in ÎŒmol g -1 DM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This view is supported by Amin et al [69] who have recently reported a decrease in specific activities of measured enzymes during decomposition of maize roots as compared to leaf residues and ascribed it to the presence of higher ligno-cellulosic fractions of the roots besides other chemical features of the wall constituents. Further, lower enzymatic activities does not necessary reflect lower efficiency [70] and we hypothesize that higher efficiency of the enzymes in Jatropha press cake amended soil might have resulted in more resource allocation to increase biomass by some group of microorganisms for ecological or competitive advantage over others.…”
Section: Influence Nutrient Amendments On Soil Organic Carbon Accumulmentioning
confidence: 59%
“…In addition, it was reported that the chemistry of a single litter type diverged when it was decomposed in management systems with distinct decomposer communities (Wickings et al, 2012).Collectively, these investigations may provide an explanation for the results that the k m value for the roots was significantly higher under the aerobic condition compared with the flooded condition. Furthermore, it was reported that the enzyme activity was higher in maize leaf than root amended soils while enzyme efficiency was systematically higher in the presence of roots, which demonstrated that litter quality is regulating decomposer strategy (Amin et al, 2014). Thus, the opposite pattern of differed process of decomposition between leaves and roots under aerobic and flooded condition indicated that the chemistry of different litter types diverged, rather than converged, during decomposition due to the activities of decomposers, as suggested by Wickings et al (2012).…”
Section: Decomposition Dynamics Of Rice Residues Under Aerobic and Flmentioning
confidence: 96%